Goldenhar syndrome with rare clinical features - Vineet Relhan; Shankila Mittal; Khushbu Mahajan; Vijay Kumar Garg (Wolters Kluwer Medknow Publications, 2017)
Goldenhar syndrome is an uncommon syndrome with malformations of first and second branchial arches. Accessory tragus is a constant feature of this syndrome but may be associated with other syndromes as well. We report a case with a combination of rare findings, i.e., multiple bilateral preauricular skin tags with short stature and mental retardation with maintained facial symmetry.